tTEM20AAR: a benchmark geophysical data set for unconsolidated fluvioglacial sediments - Néven, Alexis; Kumar Maurya, Pradip; Vest Christiansen, Anders; Renard, Philippe (My University, 2021)
Quaternary deposits are complex and heterogeneous. They contain some of the most abundant and extensively used aquifers. In order to improve the knowledge of the spatial heterogeneity of such deposits, we acquired a large (1500 ha) and dense (20 m spacing) time domain electromagnetic (TDEM) data set in the upper Aare Valley, Switzerland (available at https://doi.org/10.5281/zenodo.4269887; Neven et al., 2020). TDEM is a fast and reliable method to measure the magnetic field directly related to the resistivity of the underground. In this paper, we present the inverted resistivity models derived from this acquisition. The depth of investigation ranges between 40 and 120 m, with an average data residual contained in the standard deviation of the data. These data can be used for many different purposes: from sedimentological interpretation of quaternary environments in alpine environments, geological and hydrogeological modeling, to benchmarking geophysical inversion techniques.